DEVELOPMENT ACCELERATION POLICY IN THE LATEST AREAS: FROM THE ROADS TO THE TRANSPORTATION MACHINE - Prabowo, Hadi (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
The Mentawai Islands is one of the districts included in the 3T, least developed, and outermost zones. The situation made various parties try to free the Mentawai Islands from the shadows of the 3T region. One of them is the acceleration of infrastructure development in the Mentawai Islands. Some examples of accelerated regional development that have been carried out by the government are by improving bridges and road transportation facilities. The author sees that there are still several obstacles that become a massive task of various elements to determine the direction of accelerating development in the Mentawai Islands. The condition of the Trans Mentawai road has indeed become a major government program at this time, which is an essential element to accelerate development. The authors' findings state that there are still several areas that do not agree with the presence of the Mentawai trans. These include areas that are still thick with cultural traditions, rituals, or traditional villages of the Mentawai. The still limited budget of funds and construction work and the existence of the trans-Mentawai that not all villages will be able to benefit because it is far from the access.